A study on staphylococcal mastitis in cows - Ali Rişvanlı; Cahit Kalkarı (Eurasian Journal of Veterinary Sciences)
In this study, prevalence of Staphylococcal mastitis was investigated in the cows. A total of 1249 cows aged between 2-16 served as subjects. Presence of staphlococcal mastitis was determined by clinical examination. CMT and microbiological tests. In the conclusion, the rate of Staphylococcal mastitis was found to be 82,02% in this study. The bacteria causing this kind ol mastitis. Staph, aureus, occupied the most important part at the rate of 73,78%. Besides. Staphylococcal mastitis were determined at the minimum rate of 73.44% in the animals at the first lactation and 61.60% in the summer time. The rate of this kind of mastitis was found at maximum in the age group of 5-8 (85.15%), in the hand milking animals (82.74%). Tere is no (statistically difference as to lactation period, animal breeds and milk yield.